TEM observations of the vesicular structures and cell wall-plasma membrane interface ultrastructure of N. benthamiana epidermal cells in p33-expressing and control cells. - Vicken Aknadibossian (22676694) (2025)
A-B) Wild type p33-expressing cells exhibited areas where the plasma membrane (PM) moved further away from the cell wall (CW), and the space between the PM and the CW became occupied with vesicles (orange bars), compared to other areas of the cell (blue bars). C) A higher magnification of the vesicles in (B), exhibiting what appear to be SMVs ranging between 50-1000 nm in diameter. D) Another example of an extracellular space filled with SMVs and an example of a DMV. E) An MVB filled with SMVs that appears to open into the extracellular space between the PM and CW. F) A control cell expressing only an empty-vector expression cassette and the p22 VSR in which the PM is in close proximity to the CW, and no vesicles or MVBs are observed in the space between the PM and the CW.